Is early postoperative administration of pregabalin beneficial for patients with lung cancer?—randomized control trial - Miyazaki, Takuro; Sakai, Tetsuya; Sato, Shuntaro; Yamasaki, Naoya; Tsuchiya, Tomoshi; Matsumoto, Keitaro; Kamohara, Ryotaro; Hatachi, Go; Doi, Ryoichiro; Nagayasu, Takeshi (Journal of Thoracic Disease, 2016)
Background: Post-thoracotomy pain is an obstacle for lung-cancer patients even after introduction of less invasive surgical procedures. The aim of this prospective study was to evaluate if early postoperative administration of pregabalin is beneficial for patients with non-small cell lung cancer (NSCLC). Methods: We conducted a randomized open control trial. Patients with NSCLC were allocated randomly to epidural and nonsteroidal anti-inflammatory drug (NSAID) use for analgesia (control group) or pregabalin use (pregabalin group). Primary endpoint was the frequency of additional administration of a NSAID. Secondary endpoints were intensity of ongoing pain, frequency of neuropathic pain, and pain catastrophizing. Results: Seventy-two patients were registered and allocated. Thirty-four cases in the control group and 33 in the pregabalin group were assessed. Age, sex, body mass index (BMI), type of surgical procedure, type of lymph-node dissection, operation time, bleeding, duration of chest-tube insertion, and postoperative hospital stay between the two groups was not significantly different. Frequency of additional NSAID use between the control group (2±4 suppositories) and pregabalin group (2±3 suppositories) was not significantly different (P=0.62). Numeric Rating Scale (NRS) for the intensity of ongoing pain, frequency of neuropathic pain, and Pain Catastrophizing Scale (PCS) between each group were not significantly different at any time until 3 months after surgery. Conclusions: Early postoperative administration of pregabalin is not beneficial for patients with NSCLC.